MrTPS3 and MrTPS20 Are Responsible for β-Caryophyllene and α-Pinene Production, Respectively, in Red Bayberry (Morella rubra) - Wang, Yan; Yang, Qinsong; Zhu, Yifan; Zhao, Lan; Ju, Pengju; Wang, Guoyun; Zhou, Chaochao; Zhu, Changqing; Jia, Huijuan; Jiao, Yun; Jia, Huimin; Gao, Zhongshan (Frontiers in Plant Science, 2022)
Red bayberry is a sweet, tart fruit native to China and grown widely in the south. The key organic compounds forming the distinctive aroma in red bayberry, are terpenoids, mainly β-caryophyllene and α-pinene. However, the key genes responsible for different terpenoids are still unknown. Here, transcriptome analysis on samples from four cultivars, during fruit development, with different terpenoid production, provided candidate genes for VOC production. Terpene synthases (TPS) are key enzymes regulating terpenoid biosynthesis, and 34 TPS family members were identified in the red bayberry genome. MrTPS3 in chromosome 2 and MrTPS20 in chromosome 7 were identified as key genes regulating β-caryophyllene and α-pinene synthesis, respectively, by qRT-PCR. Subcellular localization and enzyme activity assay showed that MrTPS3 was responsible for β-caryophyllene (sesquiterpenes) production and MrTPS20 for α-pinene (monoterpenes). Notably, one amino acid substitution between dark color cultivars and light color cultivars resulted in the loss of function of MrTPS3, causing the different β-caryophyllene production. Our results lay the foundation to study volatile organic compounds in red bayberry and provide potential genes for molecular breeding.